Methodological strategies for the determination of nutrient requirements in finfish - Izquierdo M.; Robaina L. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
As aquaculture production increases, species diversification is becoming more important for the sustainability of Mediterranean Aquaculture. Since its main goal is to efficiently convert feeds into fish, studies addressed to define the nutritional requirements of candidate species are essential for the development of their culture techniques. A considerable amount of research has been devoted to study the nutritional requirements for the major cultivated finfish species. However, differences in requirements definition are frequently found in the literature, thus, it is difficult to say whether this variation in the data is simply due to methodological differences or the result of species-specific differences. Therefore, it is important to standardize experimental methods when studying a new species, accompanying all data with the experimental conditions employed. Comparison of different methodologies and experiences on different species are discussed in this study to better illustrate the possible strategies for the determination of qualitative and quantitative requirements in finfish.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)